The Sustainability (Environmental and Economical) impact of upgrading Bahrain building regulations for affordable housing units: Case study in Bahrain - Al-Saffar, May (2014)
According to World Population Review, Bahrain population is estimated to be around 1,336,250 people and it’s expected to grow further till 2100. The rapid increase of population and continues growth of cities in Bahrain leads to significant pressure on the ministry of housing to expand their housing development projects to serve the present and future population needs. However, fast growth of cities and construction development will form a pressure on the energy demand and consequently on the environment and will contribute in the global warming due to the increase of carbon footprint. In addition to that, the Ministry of Electricity and Water states that Bahrain generates annually average of 3190 MWh and the consumption is estimated to be almost 266 MWh and for each standard household it almost 132 MWh that is 50 % of the overall electricity energy produced. All the above facts as well as the climate classification of Bahrain as hot and arid region is considered to be kick off to move towards a sustainable and green development to reduce the negative impacts on the environment. Likewise, most of the GCC states are facing similar pressures that lead them to establish a sustainable building assessment certification to enhance their construction industry and the overall environment. For instance, the UAE generated the PRS - Pearl rating system, and the DGBR - Dubai Green building regulation. Also Qatar developed the QSAS – Qatar Sustainability Assessment System but not Bahrain. All the assessment systems are a combination of best practices extracted from international rating systems and customized to the unique conditions and requirements of its state of origin such as the local environment, culture and policies. Therefore, the research aims to explore the impact of upgrading the building envelope on reducing the consumption of annual energy, chiller energy and CO2 emissions in a typical housing unit in Bahrain. IES – VE simulation software was used to conduct number of evaluations to assess potential energy saving. The study covered 13 case scenarios upgrading the building envelop using specific U- values as recommended by selected regional sustainability assessments and also it tested upgrading each element of wall, roof and glazing separately to understand the impact of each on saving total energy consumption. Furthermore, it has proposed 3 new scenarios that is based on the available construction materials in the local Bahraini market. All the studied cases were an initial study to estimate the optimal case that can be integrated in the Ministry of Housing construction manual to save maximum percentage in the chiller energy, overall energy and the CO2 emissions. Page | V The collected results were compared to the current situation in Bahrain (Base Case) and it comes to the conclusion that upgrading the wall is the most beneficial building envelope element that can reduce the chiller energy, overall energy and the CO2 emissions more than the roof that is already insulated and the windows that are relatively having a low window to wall ratio. Moreover, the wall its considered as the largest surface area with poor current thermal properties and can achieve up to 21.6% reduction in chiller energy consumption and 10.8% in both overall energy consumption and CO2 emissions. This reduction was achieved by using the special dynamic wall recommended by QSAS and by using the external wall insulation system with plaster that was proposed by the author based on the available construction materials in the local Bahraini market. For that the best option will be insulating the walls externally because it’s easier to be integrated to the Ministry of Housing construction manual and for sure it going to be cheaper that changing the entire wall data as recommended by QSAS.